(untitled) (International Journal of Current Engineering and Technology, 2014)
This work intends to present the analysis of buckling of piles fully embedded on ground and subject to axial force in compression based on the Finite Element Method. The approach of eigen values is used for calculation of buckling forces of piles within this method. To calculate the critical buckling force by use of Finite Element Method the SAP 2000 software is utilized where a reinforced concrete pile of circular cross section, D=30cm, concrete class C-25/30, of 5m length, the modulus of elasticity of soil, k=1000kN/m2, with pinned end conditions (p-p) on the head and on the tip, is considered. The constant modulus of soil reaction is adopted throughout the depth. The comparison of amount of the pile buckling force obtained from software SAP 2000 with its theoretical value and by Euler’s force is done.